Range and trophic niche overlap of two sympatric species of floral oil collecting bees in a fragment of dry forest - Martins, Herbeson O. J.; Dórea, Marcos C.; Ferreira, Vinina S.; Silva, Cláudia I.; Alves-dos-Santos, Isabel (Frontiers in Bee Science, 2024)
Plant-pollinator interactions constitute complex mutualistic relationships responsible for the maintenance of the reproduction of flowering plants in different biomes. The genus Centris stands out as one of the main groups of pollinators in the Neotropical region. These bees have a close relationship with floral oil-producing plants, using this resource in the construction of their nests and/or larval feeding. The aim of the present study was to compare the resources exploited by Centris perforator and Centris xanthomelaena and assess the established trophic relationships of these two species in a fragment of dry forest (Caatinga domain). For such, direct observations were made at the flowers and analyses were performed of the pollen load on the body of female bees and the content of the larval provisions in the nests. A strong association was found between the two bee species and plants with poricidal anthers of the genus Chamaecrista, which accounted for more than half of the larval diet in both species. Samples of the pollen load of C. xanthomelaena exhibited a greater diversity of pollen types. While Rhaphiodon echinus was a constant source of nectar for C. xanthomelaena, C. perforator females collected nectar from plants of short, rapid flowering, such as Cenostigma microphyllum and Tabebuia aurea. Malpighia emarginata was the main source of floral oil for both species. However, C. xanthomelaena also interacted with Angelonia connigera and Krameria sp. to obtain this resource. The similarity in the trophic niche of the species was 57% in the subsamples of pollen on the body of females and 46% for larval provision. The results showed that areas of native vegetation are essential for bee populations in regions with agricultural activity, ensuring a regular supply of ecological resources for these bees.